Relationship of Ferritin Levels and Vitamin B12 Levels Pregnant Women Anemia on Baby Birth Weight - Citra Dewi Anitasari; Arni Amir; Defrin Defrin (Universitas Andalas, 2018)
Anemia in pregnancy is a health problem that usually occurs throughout the world. In developing countries, anemia during pregnancy is due to micronutrient deficiencies such as iron, vitamin B12 and folic acid. This was cross sectional study. The population of this study were all anemic pregnant women who came to Lubuk Buaya Health Center. The sample in this study based on inclusion criteria totalling 40 respondents taken by consecutive sampling technique. Examination of ferritin and vitamin B12 levels was carried out at the Andalas University Biomedical Laboratory using the ELISA method. Statistical test was performed using SPSS, normality test with Shapiro Wilk andSpearman test to see the relationship between ferritin and vitamin B12 levels to the baby's birth weight.The results of this study showed that the mean ferritin level of anemia pregnant woman with baby birth weight was 11.13 ± 6.37 with a value of p> 0.05, r = 0.280 and the mean vitamin B12 levels of anemic pregnant women with birth weight were 299, 53 ± 98.46 with a value of p> 0.05, r = 0.161.The conclusion of this study was that there is a non significant positive relationship between ferritin and vitamin B12 levels on the birth weight of the baby. It is recommended that pregnant women keep on consuming Fe tablets during pregnancy and further study is necessary to see pregnant woman adherence in consuming Fe tablets.